The Business of Software In Praise of Bad Programmers. - Armour, Phillip G. (Communications of the ACM, 2010)
The author discusses the advantages of a team approach in software programming. He mentions his experience of managing a team that included a low-level programmer. The team defined the metrics for success necessary for each team member. Although the programmer did not measure up, the manager found that the team improved when they had to define their process to support their weaker team member. He mentions that the team was able to overcome individual limitations while not sacrificing individuality and creativity.